2009
DOI: 10.4103/1817-1737.56012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors predisposing anastomotic leak after transhiatal esophagectomy

Abstract: OBJECTIVE:The objective of our study was to identify the incidence and risk factors of anastomotic leaks following transhiatal esophagectomy (THE).MATERIALS AND METHODS:A prospective study was conducted on 61 patients treated for carcinoma of the esophagus between 2006 and 2007. We examined the following variables: age, gender, preoperative cardiovascular function, intraoperative complications such as hypotension, arrhythmia, mediastinal manipulation period, blood loss volume, blood transfusion, duration of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…In our study, intra-operative blood transfusion was associated with post-operative complications. Similarly, multiple investigations showed that intra-operative blood transfusion increased post-operative complications (12,(14)(15)(16)23). Various publications have shown that blood transfusion is a factor that increases mortality (7,8,14,24), whereas our findings indicated that blood transfusion increases complications, but not mortality.…”
Section: Intra-operative Blood Transfusionsupporting
confidence: 69%
See 1 more Smart Citation
“…In our study, intra-operative blood transfusion was associated with post-operative complications. Similarly, multiple investigations showed that intra-operative blood transfusion increased post-operative complications (12,(14)(15)(16)23). Various publications have shown that blood transfusion is a factor that increases mortality (7,8,14,24), whereas our findings indicated that blood transfusion increases complications, but not mortality.…”
Section: Intra-operative Blood Transfusionsupporting
confidence: 69%
“…Anastomosis leakage is considered as one of the most important and serious surgical complications, that can result in mediastinal infection and sepsis. In our study, the rate of anastomosis leakage and fistula was 6.30%, and it ranged between 3%-21.3% in other investigations (4,7,15,16). We found no significant association between anastomosis leakage and mortality, that may be due to anastomosis being located in the neck in most surgeries, which has a lower risk of mediastinitis.…”
Section: Medical Complications Anastomosis Leakage and Fistula Formationcontrasting
confidence: 50%
“…The present study identifies the potential non-surgical risk factors associated with anastomotic leakage after major abdominal surgery. Although many studies are available in the literature[ 3 4 5 ] on the role of surgical factors causing anastomotic leakage, very few studies have identified the role of non-surgical factors which are independently associated with increased risk of anastomotic leakage. The most important pathophysiological basis for anastomotic leakage is believed to be ischemia of the gut conduit.…”
Section: Discussionmentioning
confidence: 99%
“…An important factor explaining the wide range of the incidence of AL is the large variety in the definition of this complication throughout the literature [14]. Although the exact etiopathogenesis of AL has not yet been clarified, numerous risk factors for developing this complication have been recognized [15,16,17]. Among others, preoperative weight loss, perioperative blood loss, and longer operative time have been shown to be persistent risk factors across different studies [16,18,19,20].…”
Section: Introductionmentioning
confidence: 99%